On Log-Likelihood-Ratios and the Significance of Rare Events - Moore, Bob (Association for Computational Linguistics, 2004)
We address the issue of judging the significance of rare events as it typically arises in statistical natural-language processing. We first define a general approach to the problem, and we empirically compare results obtained using log-likelihood-ratios and Fisher's exact test, applied to measuring strength of bilingual word associations.